Investigating the evolution of major Northern Hemisphere ice sheets during the last glacial-interglacial cycle - S. Bonelli; S. Charbit; M. Kageyama; M.-N. Woillez; G. Ramstein; C. Dumas; A. Quiquet (Copernicus Publications, 2009)
A 2.5-dimensional climate model of intermediate complexity, CLIMBER-2, fully coupled with the GREMLINS 3-D thermo-mechanical ice sheet model is used to simulate the evolution of major Northern Hemisphere ice sheets during the last glacial-interglacial cycle and to investigate the ice sheets responses to both insolation and atmospheric CO 2 concentration. This model reproduces the main phases of advance and retreat of Northern Hemisphere ice sheets during the last glacial cycle, although the amplitude of these variations is less pronounced than those based on sea level reconstructions. At the last glacial maximum, the simulated ice volume is 52.5×10 15 m 3 and the spatial distribution of both the American and Eurasian ice complexes is in reasonable agreement with observations, with the exception of the marine parts of these former ice sheets. A set of sensitivity studies has also been performed to assess the sensitivity of the Northern Hemisphere ice sheets to both insolation and atmospheric CO 2 . Our results suggest that the decrease of summer insolation is the main factor responsible for the early build up of the North American ice sheet around 120 kyr BP, in agreement with benthic foraminifera δ 18 O signals. In contrast, low insolation and low atmospheric CO 2 concentration are both necessary to trigger a long-lasting glaciation over Eurasia.